FAKTOR PENYEBAB KETIDAKMAMPUAN PETANI MEMENUHI PERMINTAAN BABYBUNCIS UNTUKPT. ALAMANDA SEJATI UTAMA SERTASTRATEGI UNTUK MENGATASINYA (Studi Kasus Kelompok Tani Tauhid, Kabupaten Bandung Barat) - KARTIWA, NUR ANNISA RIZKITA; DJUWENDAH, ENDAH (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2016)
Baby Kenya bean is a bean types that has a good prospects, it has successfully entered the export market. Poktan Tauhid which is a part of the Farmers Group (Gapoktan) Lembang Agri are the farmers group who grows baby kenya bean. The aim of this research are to know the causative factors of farmer that led to an inability to meet the demand for the baby kenya bean for PT. Alamanda Sejati Utama and determine the accurate strategy which can be implemented in Poktan Tauhid to overcome the problems.The research design is qualitative with descriptive analysis technique with fishbone diagrams and analysis of operation strategies with QSPM. The results of the research indicates that a very problematic technical factors among others are the weather conditions, pest and plant disease. While non-technical factors that is very problematic isthe harvest labor. In addition, technical factors that enter into the troubled category are technology, seeds, water availability andthe wind. The alternative strategy that can be implemented in Poktan Tauhid Backward Integration.The implication of this alternative strategy is enabling Poktan Tauhid to better control the process to reschedule planting schedules for every babykenya bean farmer. Moreover, counseling should be given more frequently, related to technologies and the prevention of pests and diseases naturally.Keyword :Causative factors, alternative strategy, baby kenya bean